Understanding consumer’ switching intention toward traceable agricultural products: Push‐pull‐mooring perspective - Nguyen, Thi Hong Nhung; Yeh, Quey‐Jen; Huang, Ching‐Ying (International journal of consumer studies, 2022)
Food traceability systems (FTSs) have been increasingly implemented in the food supply chain as a feasible solution to categorize the safety and quality of food. Governments across the world are striving to build public trust and to shift demand to traceable agricultural products (TAPs). This article stresses an important subject by focusing on consumer’ switching intention toward TAPs as product switching has a great impact on food producers and sellers. A total of 478 valid samples were collected from Taiwanese consumers via an online survey. By applying the Push‐Pull‐Mooring (PPM) model, the empirical results of PLS‐SEM analyses identified critical factors and their impacts on consumer switching intention: perceived risk uncertainty associated with non‐traceable food; perceived quality of TAP‐labeled food, willingness to pay a premium price, and health consciousness. Theoretically, this study sheds new light on the literature of migration studies, by examining consumer behavior toward FTSs, it is posited that the PPM theoretical model can predict switching decisions in the food sector. Practically, the findings suggested that FTS is a viable risk‐relieving strategy that should be utilized more heavily to boost consumer retention related to credible food options.